Study on the Effect and Importance of Nutritional Supplements on Productivity Enhancement in Poultry - Karrar Hussein Ali (University of Thi-Qar Journal of agricultural research, 2025)
This study aimed to evaluate the effect of various nutritional supplements on the productive performance and carcass characteristics of broiler chickens, as well as their impact on poultry health and productivity. The focus was on amino acids, vitamins, and minerals.Arandomized controlled trial (RCT) was conducted to compare the effects of dietary supplements against a control group. The experiment lasted 40 days, starting from day one to day 40, and was carried out at Al-Abbasia Field (Private Sector) under controlled environmental conditions compliant with standard poultry farming climate criteria.Control Group (n=20): Fed a basal diet with no additives.Experimental Group (n=20): Fed a basal diet supplemented with a blend of probiotics + selenium + vitamins + enzymes + amino acids.The experimental group showed a significant increase (p < 0.05) in:Final body weight (2850g vs. 2450g).Daily growth rate (71.25g/day vs. 61.25g/day).Additionally, the feed conversion ratio (FCR) improved in the supplemented group (1.65 vs. 1.85), indicating higher feed efficiency. Incorporate nutritional supplements (probiotics, enzymes, amino acids) into broiler diets to enhance growth and feed efficiency. Monitor FCR to evaluate feed utilization and adjust dietary formulations as needed.Optimize environmental conditions (temperature, humidity, ventilation) to maximize supplement efficacy.